Oncoplastic Surgery: Does Patient and Medical Specialty Influences the Evaluation of Cosmetic Results? - de Oliveira-Junior, Idam [UNESP] (2020)
Background: Oncoplastic surgery (OS) has added plastic surgery concepts and techniques to the breast cancer surgery. However, reports of the impact of OS on cosmesis after breast-conserving surgery (BCS) are limited in the literature. Patients and Methods: This cross-sectional prospective study included patients who underwent BCS. The patients self-evaluated the cosmetic outcome of the breasts and had them photographed. The photos were evaluated by BCCT.core software and by 6 breast surgeons (mastologists and plastic surgeons) using the Harvard, Garbay, and Fitoussi scales. Kappa and weighted kappa tests were used to analyze agreement for categorical variables; for continuous variables, the interclass correlation index and the chi-square test to analyze the association between the OS and the symmetrization. Results: A total of 300 patients were evaluated: 228 (76.0%) underwent traditional BCS and 72 (24.0%) underwent OS, and of these, 37 (51.4%) underwent contralateral symmetrization surgery. In the evaluation of the cosmetic result, the correlation between patients and observers (BCCT.core and surgeons) was weak; between the 2 groups of surgeons, the correlation was moderate (Fitoussi scale) and excellent (Garbay scale). Plastic surgeons are more critical for evaluating cosmetic results; they considered it good or excellent in 30.0% whereas patients, mastologists, and BCCT.core results considered it so in 78.8%, 34.0%, and 30.0%, respectively. In terms of cosmesis, OS and symmetrization did not influence the results in this study with long follow-up. Conclusion: Patients’ self-evaluation reported better cosmesis than surgeons’ analyses. Plastic surgeons were the most critical. OS and symmetrization did not influence the results.